CD4 T Cell Responses and the Sepsis-Induced Immunoparalysis State - Martin, Matthew D.; Badovinac, Vladimir P.; Griffith, Thomas S. (Frontiers in Immunology, 2020)
Sepsis remains a major cause of death in the United States and worldwide, and costs associated with treating septic patients place a large burden on the healthcare industry. Patients who survive the acute phase of sepsis display long-term impairments in immune function due to reductions in numbers and function of many immune cell populations. This state of chronic immunoparalysis renders sepsis survivors increasingly susceptible to infection with newly or previously encountered infections. CD4 T cells play important roles in the development of cellular and humoral immune responses following infection. Understanding how sepsis impacts the CD4 T cell compartment is critical for informing efforts to develop treatments intended to restore immune system homeostasis following sepsis. This review will focus on the current understanding of how sepsis impacts the CD4 T cell responses, including numerical representation, repertoire diversity, phenotype and effector functionality, subset representation (e.g. Th1 and Treg frequency), and therapeutic efforts to restore CD4 T cell numbers and function following sepsis. Additionally, we will discuss recent efforts to model the acute sepsis phase and resulting immune dysfunction using mice that have previously encountered infection, which more accurately reflects the immune system of humans with a history of repeated infection throughout life. A thorough understanding of how sepsis impacts CD4 T cells based on previous studies and new models that accurately reflect the human immune system may improve translational value of research aimed at restoring CD4 T cell-mediated immunity, and overall immune fitness following sepsis.